2018
DOI: 10.13031/trans.12516
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Effects of Droplet Size and Flow Rate on the Chargeability of Spray Droplets in Electrostatic Agricultural Sprays

Abstract: Abstract. The chargeability of liquid sprays is an important factor in determining the deposition efficiency of electrostatic pesticide sprays. The Rayleigh limit provides information on the maximum amount of charge a spray droplet can carry as a function of droplet size and liquid properties. This article reviews the literature to determine what fraction of the Rayleigh limit is achievable. Typically, less than 10% of the Rayleigh limit charge is obtained. The droplet charge per unit mass decreases with incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
(37 reference statements)
2
7
0
Order By: Relevance
“…Studies have shown that flow rate and conductivity of the dispersed phase have major effects on the droplet chargeability, which influences the droplet size. Generally, the decrease in flow rate and increase in conductivity of the sprayed liquid lead to increased droplet charge and reduced drop size . This could be significant, particularly for reactions that are limited by mass transfer due to low interfacial areas.…”
Section: Results and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Studies have shown that flow rate and conductivity of the dispersed phase have major effects on the droplet chargeability, which influences the droplet size. Generally, the decrease in flow rate and increase in conductivity of the sprayed liquid lead to increased droplet charge and reduced drop size . This could be significant, particularly for reactions that are limited by mass transfer due to low interfacial areas.…”
Section: Results and Discussionsupporting
confidence: 92%
“…Generally, the decrease in flow rate and increase in conductivity of the sprayed liquid lead to increased droplet charge and reduced drop size. 33 This could be significant, particularly for reactions that are limited by mass transfer due to low interfacial areas. In this work, various flow rates and conductivities of the aqueous dispersed phase were studied.…”
Section: Methodssupporting
confidence: 92%
“…They found no effect of different forward speeds on deposition. Although electrostatic spraying has great potential as a pesticide application technique (Post and Roten, 2018), it is necessary to continue improving this technology and to better understand the behaviour of electrostatic droplets in comparison with traditional spraying systems in vineyards (O'Donnell et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The uniformity of droplet distribution, drift, and coverage of the target are the main indicators for evaluating spray quality 17,18 . We found that droplet size, droplet volume median diameter, and droplet number median diameter strongly affected droplet deposition 19 .…”
Section: Discussionmentioning
confidence: 99%